ISOLASI MANGOSTIN DARI KULIT BUAH MANGGIS (Garcinia mangostana L.) DAN UJI AKTIVITAS ANTIBAKTERI TERHADAP Bacilus cereus. - Sri Idawati (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2018)
One of the fruit plants that has the potential as a drug is mangosteen, especially on the skin of the fruit. The main bioactive compound and become a major compound in the mangosteen plant, namely ?-mangostin. This research has succeeded in isolating ?-mangostin through the extraction process using reflux method using ethanol 96%. Purification done by the recrystallization method with solvent ethanol:aquades (1:1). The result of extraction yield 29,93% and the result of purification obtained the yield of ?-mangostin from the weight of the extract was 2,81%. Initial identification of isolates using thin layer Chromatography (TLC) and melting point test. This yellow powder isolate has a melting point of 179,7 ºC. Next, structural elucidation is carried out using FT-IR spectroscopy data. Antibacterial activity test isolate compound (?-mangostin) of Bacilus cereus bacteria have the power inhibitory with MIC 0,031 µg/ml.